2014
DOI: 10.3389/fpsyg.2014.00099
|View full text |Cite
|
Sign up to set email alerts
|

Decreased electrophysiological activity represents the conscious state of emptiness in meditation

Abstract: Many neuroscientific theories explain consciousness with higher order information processing corresponding to an activation of specific brain areas and processes. In contrast, most forms of meditation ask for a down-regulation of certain mental processing activities while remaining fully conscious. To identify the physiological properties of conscious states with decreased mental and cognitive processing, the electrical brain activity (64 channels of EEG) of 50 participants of various meditation proficiencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 88 publications
7
76
0
2
Order By: Relevance
“…The techniques are simple: (1) We do not use concentration or repetition or analysis, only the rule "do not intervene" in breathing, focusing on VBH and "letting it happen"; (2) Eyes closed/option of having them half open; (5) Static; (6) Nonverbal; (7) Sit in the correct position, backbone straight, on a chair, cushion or bench; (8) There is therapist-patient interaction. In some ways, our work is similar to the idiosyncratic meditation proposed by Hinterberger et al [122], in the sense of integrating different methods. We must add that the rule "do not intervene" is linked to another that is "let yourself breathe", whose aim is to enable the discursive mind to enter into meditative calm.…”
Section: Non-linear Dynamics Of Meditative States Of Consciousness: Asupporting
confidence: 51%
See 2 more Smart Citations
“…The techniques are simple: (1) We do not use concentration or repetition or analysis, only the rule "do not intervene" in breathing, focusing on VBH and "letting it happen"; (2) Eyes closed/option of having them half open; (5) Static; (6) Nonverbal; (7) Sit in the correct position, backbone straight, on a chair, cushion or bench; (8) There is therapist-patient interaction. In some ways, our work is similar to the idiosyncratic meditation proposed by Hinterberger et al [122], in the sense of integrating different methods. We must add that the rule "do not intervene" is linked to another that is "let yourself breathe", whose aim is to enable the discursive mind to enter into meditative calm.…”
Section: Non-linear Dynamics Of Meditative States Of Consciousness: Asupporting
confidence: 51%
“…OM appears to be related to Thoughtless Emptiness (TE) meditation in terms of the tendency to refrain from using thoughts, memories, emotions, associations, perceptions while this state is maintained [122]. This persistent focus on OM is related to the practice in Tibetan Buddhism called Samatha with regard to the use of breathing as a focus, and is extensible to other practices.…”
Section: Description Of the Three States/thresholdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheeler et al (1997) reported that in some cases lesions in the right frontotemporal cortex led to the experience of cognitive detachment from the self. Interestingly, the contrast of “selfless” with self-centered shows a very similar picture, especially with regard to alpha and beta bands, to the contrast between “thoughtless emptiness” and a state of presence referred to as open monitoring as measured in a study with 30 meditators (Hinterberger et al, 2014). In fact, the state of being present in the moment with an awareness of the physical space of the body represents the IS state, while pure observation of an object from outside (the instruction in the OF state did not ask for cognitive thoughts about the object) might come close to a non-attached thoughtless state.…”
Section: Discussionmentioning
confidence: 69%
“…It is probable that each of these state transitions, as well as other transitions not mentioned in this section (i.e., states 4 to 5 to 6), are accompanied by particular alterations in the EEG profiles of the individuals accomplishing these transitions. 97 Thus each of the proposed states may have its own electroencephalographic signature.…”
Section: Downloaded By [University Of Otago] At 00:21 14 July 2015mentioning
confidence: 99%